Algorithms and architectures for parallel processing : ICA3PP 2016 collocated workshops : SCDT, TAPEMS, BigTrust, UCER, DLMCS, Granada, Spain, December 14-16, 2016, proceedings /: ICA3PP 2016 collocated workshops : SCDT, TAPEMS, BigTrust, UCER, DLMCS, Granada, Spain, December 14-16, 2016, proceedings. (2016) - Unknown
No abstract available